Simulation of the Development Height of the Two Zones in the 23041 Working Face of Gaocheng Coal Mine - Shi, Huaiyang (International Journal of Natural Resources and Environmental Studies, 2025)
Sliding structure refers to the rock deformation process and result where the upper plate rock layers continuously slide and erode downward under the action of gravity. During the downward sliding process, after two major slides, the strata on the upper and lower sliding surfaces are both inclined in the opposite direction to the strata of the sliding body, forming an overlying strata reverse dip zone. This paper takes the 23041 working face of Gaocheng Coal Mine as the research object and develops a device for similar simulation experiments, which has applied for a national invention patent. Similar material simulation experiments and UDEC software were used to simulate the influence of different dip angles of the overlying strata reverse dip on mining fractures and surface subsidence. Based on the results of numerical simulation, the development law of mining fractures under the overlying strata reverse dip can be obtained. The research shows that the larger the dip angle of the overlying strata reverse dip, the lower the development height of the water-conducting fracture zone and the lower the height of overlying strata damage.